Comprehensive Analysis of Transcriptome-wide m6A Methylome Upon Clostridium perfringens Beta2 Toxin Exposure in Porcine Intestinal Epithelial Cells by m6A Sequencing - Zhang, Juanli; Yang, Qiaoli; Yang, Jiaojiao; Gao, Xiaoli; Luo, Ruirui; Huang, Xiaoyu; Yan, Zunqiang; Wang, Pengfei; Wang, Wei; Xie, Kaihui; Zhang, Bo; Gun, Shuangbao (Frontiers in Genetics, 2021)
Piglet diarrhea is a swine disease responsible for serious economic impacts in the pig industry. Clostridium perfringens beta2 toxin (CPB2), which is a major toxin of C. perfringens type C, may cause intestinal diseases in many domestic animals. N6-methyladenosine (m6A) RNA methylation plays critical roles in many immune and inflammatory diseases in livestock and other animals. However, the role of m6A methylation in porcine intestinal epithelial (IPEC-J2) cells exposed to CPB2 has not been studied. To ad-dress this issue, we treated IPEC-J2 cells with CPB2 toxin and then quantified methylation-related enzyme expression by RT-qPCR and assessed the m6A methylation status of the samples by colorimetric N6-methyladenosine quantification. The results showed that the methylation enzymes changed to varying degrees while the m6A methylation level increased (P < 0.01). On this basis, we performed N6-methyladenosine sequencing (m6A-seq) and RNA sequencing (RNA-seq) to examine the detailed m6A modifications and gene expression of the IPEC-J2 cells following CPB2 toxin exposure. Our results indi-cated that 1448 m6A modification sites, including 437 up-regulated and 1011 down-regulated, differed sig-nificantly between CPB2 toxin exposed cells and non-exposed cells (P < 0.05). KEGG pathway analysis results showed that m6A peaks up-regulated genes (n = 394) were mainly enriched in cancer, Cushing syn-drome and Wnt signaling pathways, while m6A peaks down-regulated genes (n = 920) were mainly associ-ated with apoptosis, small cell lung cancer, and the herpes simplex virus 1 infection signaling pathways. Furthermore, gene expression (RNA-seq data) analysis identified 1636 differentially expressed genes (DEGs), of which 1094 were up-regulated and 542 were down-regulated in the toxin exposed group com-pared with the control group. In addition, the down-regulated genes were involved in the Hippo and Wnt signaling pathways. Interestingly, the combined results of m6A-seq and RNA-seq identified genes with up-regulated m6A peaks but with down-regulated expression, here referred to as ‘hyper-down’ genes (n=18), which were mainly enriched in the Wnt signaling pathway. Therefore, we speculated that the genes in the Wnt signaling pathway may be modified by m6A methylation in CPB2-induced IPEC-J2 cells. These findings provide new insights enabling further exploration of the piglet diarrhea caused by CPB2 toxin.